EDUKASI MANFAAT SUNGKAI SEBAGAI SALAH SATU TANAMAN OBAT UNTUK MENINGKATKAN DAYA TAHAN TUBUH DI NAGARI SIPINANG PALEMBAYAN KABUPATEN AGAM - Dillasamola, Dwisari; Aldi, Yuffri; Nasif, Hansen; Alen, Yohannes; Syofyan, Syofyan; Sayyida, Alya (BULETIN ILMIAH NAGARI MEMBANGUN, 2024)
Sungkai (Peronema canescens Jack) is one of the herbal plants used by the community to increase endurance and as a traditional medicine for various diseases. This plant is abundant in West Sumatra and has great potential as an immunostimulant. This aims to educate the public about the benefits of Sungkai and promote a healthy lifestyle. This community service activity was carried out in Kenagarian Sipinang, Agam Regency, by involving PKK women and the local community. The methods used included counselling on the benefits of Sungkai leaves, filling out questionnaires before and after counselling, and interactive discussions. The results of the education programme showed an increased understanding of the benefits of Sungkai, especially as an immunostimulant. Data from the questionnaire showed that only 40% of the total respondents knew that Sungkai could be used to increase immunity. The majority of respondents, 25%, were more familiar with Sungkai without knowing its health potential. After the implementation of the education programme, there was a significant increase in the community's understanding of the benefits of Sungkai. From the questionnaire results collected, it was found that 100% of the respondents reported increased knowledge about the various benefits of Sungkai, which can increase endurance and the community began to be interested in using sungkai leaves as medicine. Education on local medicinal plants such as Sungkai has proven to be effective in improving the health of the community.